73 POSSIBLE NEW TREATMENT MODALITY FOR ATRIAL FIBRILLATION. (1st March 2007) - Agarawal, N.; Fissha, M. Z.; Baltazar, R.; Cummings, C.; Mower, M. M.
Abstract : Application of cold to the epicardial surface of the atrium was shown to reverse acetylcholine-induced atrial fibrillation to sinus rhythm in animal models. Varying the intensity of the cold gives a graded response with respect to time, and it appears that about one-sixth of the atrial surface is needed to effect this response. Intravenous cold saline solution has also been found to be effective for cardioversion of atrial fibrillation in dogs induced by atrial pacing in the presence of increased adrenergic tone. The following clinical episode supports the concept that the use of cold could be a possible new treatment modality for atrial fibrillation in humans. A 30-year-old African American male with ventricular septal defect was brought to the catheterization laboratory for left and right heart catheterization and ventriculography. Prior to the procedure, he was placed on telemetry, which revealed atrial fibrillation. This was a new finding as multiple prior ECGs had consistently shown sinus rhythm. During the catheterization, he was injected twice with a bolus of cold saline for cardiac output determination using thermal dilution. After the second injection, it was observed that the atrial fibrillation instantly terminated and did not recur. Coronary angiography revealed normal coronary arteries. The patient was discharged on Coumadin as prophylaxis against stroke and was discontinued after 6 months. This episode suggests that intravenous injection of cold saline may be effective in cardioversion of human atrial fibrillation. An implanted device therapy based on application of cold to the atrium may be possible from either the endocardial or the epicardial surfaces.